RISK FACTORS AND INCIDENCE OF PNEUMOTHORAX AFTER ULTRASOUND-GUIDED THORACENTESIS - SARDAR, K; SAFDAR, SS; TARAR, JM; KHAN, S; NAQVI, S (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in tertiary care hospitals between June 2021 and June 2022 to evaluate the risk factors and occurrence of pneumothorax after ultrasound-guided thoracentesis. The study included subjects with pleural effusion in whom pre-procedural thoracentesis under ultrasound guidance was performed. Outcomes were recorded, including chest tube insertion, rate of re-expansion of lungs, length of hospital stay, ICU admission, and mortality rate. Results showed that 500 65 (13%) patients developed pneumothorax. The most frequent etiologies of pleural were congestive heart failure (21%) and malignancy (55%). Multivariate analysis showed an independent association between the volume of pleural fluid drained and the occurrence of thoracentesis-associated pneumothorax (Odds ratio 1.002, 95% Confidence interval 1–1.002; P=.042). It was concluded that pre-procedural thoracentesis under US guidance is associated with a relatively high incidence of pneumothorax. Drainage of a larger volume of pleural fluid is a significant risk factor for developing pneumothorax.